2014
DOI: 10.1038/jp.2014.165
|View full text |Cite
|
Sign up to set email alerts
|

Rescuer fatigue during simulated neonatal cardiopulmonary resuscitation

Abstract: Similarly, 3:1 C:V and CCaV CPR were also fatiguing. We recommend that rescuers should switch after every second cycle of heart rate assessment during neonatal CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 30 publications
(45 reference statements)
5
44
1
Order By: Relevance
“…A recent randomized animal trial comparing CC+SI using CC rates of 90/min versus 120/min reported a similar time to ROSC and survival rate, and similar hemodynamic and respiratory parameters during CPR [17], suggesting that higher CC rates are not necessarily an advantage. In addition, recent simulation studies assessing fatigue reported that operators using CC rates of 120/min compared to 90/min showed signs of fatigue within 2 min of initiating CC [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized animal trial comparing CC+SI using CC rates of 90/min versus 120/min reported a similar time to ROSC and survival rate, and similar hemodynamic and respiratory parameters during CPR [17], suggesting that higher CC rates are not necessarily an advantage. In addition, recent simulation studies assessing fatigue reported that operators using CC rates of 120/min compared to 90/min showed signs of fatigue within 2 min of initiating CC [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Leaning decreased with time during continuous CC, suggesting that either leaning is not caused by rescuer fatigue, or that it may be mitigated by automated feedback during CPR. Our own observations from manikin studies also suggest leaning during neonatal CPR,34 however this has not been systematically analysed.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the optimal frequency of CCs in both children and adults is not specified [21][22][23]. Li et al [24] showed that even though it was possible for neonatal staff to perform continuous CCs at rates of 90 and 120 × min -1 , a significant decay in CC pressure occurred after 96 s and 72 s, respectively. Moreover, when CPR was performed with the standard 3:1 compression:ventilation (C:V) ratio, a significant decay occurred only after 156 s. According to Li et al [24], good quality CCs might be maintained for more than twice as long in 3:1 C:V CPR compared with uninterrupted CCs at the rate of 120 × min -1 (CCaV-120).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [24] showed that even though it was possible for neonatal staff to perform continuous CCs at rates of 90 and 120 × min -1 , a significant decay in CC pressure occurred after 96 s and 72 s, respectively. Moreover, when CPR was performed with the standard 3:1 compression:ventilation (C:V) ratio, a significant decay occurred only after 156 s. According to Li et al [24], good quality CCs might be maintained for more than twice as long in 3:1 C:V CPR compared with uninterrupted CCs at the rate of 120 × min -1 (CCaV-120). In addition, the three-minute CC depth decline was 50% if CCs were performed at the rate of 120 × min -1 vs. 30% if they were performed at the rate of 90 × min -1 .…”
Section: Discussionmentioning
confidence: 99%